The Economic Significance of Investment Activity and Its Place in The Economy of Uzbekistan - Yusupova Jamila Karamatdinovna (Zien Journals, 2021)
This article provides information on the economic content of investment activities, its role as an important factor in ensuring sustainable economic growth and public administration in pursuing an active investment policy, as well as investment processes in the economy of Uzbekistan.
Keywords: Investment; object; subject; public investment program